2018
DOI: 10.1002/cncy.22003
|View full text |Cite
|
Sign up to set email alerts
|

Anal cytological lesions and HPV infection in individuals at increased risk for anal cancer

Abstract: The prevalence of anal cytological lesions is high in MSM, even in HIV-infected individuals treated with combined antiretroviral therapy. In these subjects, HSILs occur more frequently and at a younger age in comparison with HIV-uninfected counterparts. Specific diagnostic procedures should be implemented to manage individuals at increased risk for anal cancer with an abnormal anal Papanicolaou test. Cancer Cytopathol 2018. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 44 publications
1
25
1
Order By: Relevance
“…ART vs. ART naïve (26, 27, 32-35, 102-104, 107-112, 116-122, 124 Nadir CD4+ ≥200 vs. <200 cells/µl (27,102,105,106,108…”
Section: Ascus-ain1+ Prevalencementioning
confidence: 99%
“…ART vs. ART naïve (26, 27, 32-35, 102-104, 107-112, 116-122, 124 Nadir CD4+ ≥200 vs. <200 cells/µl (27,102,105,106,108…”
Section: Ascus-ain1+ Prevalencementioning
confidence: 99%
“…A recent study by Dona et al reported lower CD4 counts and CD4 nadir in patients with anal dysplasia, but these parameters were without statistical significance . Multiple studies have examined and reported a correlation between these parameters and anal dysplasia .…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, there were approximately 8200 new cases with approximately 1100 deaths reported in the United States, and the disease is more common in women than men, with a ratio of 1.8:1 . Both HIV‐positive (HIV+) and HIV‐negative (HIV‐) individuals with high‐risk HPV infection, in particular HPV types 16/18, were found to be 2 to 4 times more likely to have cytological lesions compared with those who were negative for these genotypes . An HPV infection is prevalent, and approximately 90% of people living with HIV (PLWH) also are HPV positive.…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation is that the presence and effect of low-risk HPV types could not be evaluated with the genotyping test used in our study. However, although it has been suggested that low-risk HPV types may have a role in the appearance of anal lesions, the risk of low-risk HPV infection in the development and progression of anal premalignancies is clearly lower than the risk due to high-risk HPV infection [44,45].…”
Section: Discussionmentioning
confidence: 99%